Results from a proactive follow-up intervention to improve linkage and retention among people living with HIV in Uganda: a pre-/post- study - Caroline E. Boeke; Vennie Nabitaka; Andrea Rowan; Katherine Guerra; Pamela Nawaggi; Vivienne Mulema; Victor Bigira; Eleanor Magongo; Patricia Mucheri; Andrew Musoke; Cordelia Katureebe (BMC, 2018)
Abstract Background Despite gains in HIV testing and treatment access in sub-Saharan Africa, patient attrition from care remains a problem. Evidence is needed of real-world implementation of low-cost, scalable, and sustainable solutions to reduce attrition. We hypothesized that more proactive patient follow-up and enhanced counseling by health facilities would improve patient linkage and retention. Methods At 20 health facilities in Central Uganda, we implemented a quality of care improvement intervention package that included training lay health workers in best practices for patient follow-up and counseling, including improved appointment recordkeeping, phone calls and home visits to lost patients, and enhanced adherence counseling strategies; and strengthening oversight of these processes. We compared patient linkage to and retention in HIV care in the 9 months before implementation of the intervention to the 9 months after implementation. Data were obtained from facility-based registers and files and analysed using multivariable logistic regression. Results Among 1900 patients testing HIV-positive during the study period, there was not a statistically significant increase in linkage to care after implementing the intervention (52.9% versus 54.9%, p = 0.63). However, among 1356 patients initiating antiretroviral therapy during the follow-up period, there were statistically significant increases in patient adherence to appointment schedules (44.5% versus 55.2%, p = 0.01) after the intervention. There was a small increase in Ministry of Health-defined retention in care (71.7% versus 75.7%, p = 0.12); when data from the period of intervention ramp-up was dropped, this increase became statistically significant (71.7% versus 77.6%, p = 0.01). The increase in retention was more dramatic for patients under age 19 years (N = 84; 64.0% versus 83.9%, p = 0.01). The cost per additional patient retained in care was $47. Conclusions Improving patient tracking and counseling practices was relatively low cost and enhanced patient retention in care, particularly for pediatric and adolescent patients. This approach should be considered for scale-up in Uganda and elsewhere. However, no impact was seen in improved patient linkage to care with this proactive follow-up intervention. Trial registration Pan African Clinical Trial Registry #PACTR201611001756166. Registered August 31, 2016.